2006
DOI: 10.1590/s1516-89132006000600002
|View full text |Cite
|
Sign up to set email alerts
|

Copper improves the production of laccase by the white-rot fungus Pleurotus pulmonarius in solid state fermentation

Abstract: Pleurotus pulmonarius (Fr)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 19 publications
(16 reference statements)
3
29
0
2
Order By: Relevance
“…A stimulatory effect of Zn on laccase activity, noted in P. ostreatus HAI 494, was also demonstrated in Trametes versicolor and T. hirsuta (Collins and Dobson 1997;Keum and Li 2004), while in P. pulmonarius HAI 572 and other tested strains, as well as in T. pubescens this element reduced the activity (Galhaup and Haltrich 2001;Tychanowicz et al 2006), which could be explained by species specificity. Laccase induction could be the result of limited selectivity of the metal-responsive promoter in the laccase gene in P. ostreatus, in which transcription can be controlled by several metal ions, including Zn (Faraco et al 2003).…”
Section: Effect Of Trace Elements On Laccase Activitymentioning
confidence: 73%
“…A stimulatory effect of Zn on laccase activity, noted in P. ostreatus HAI 494, was also demonstrated in Trametes versicolor and T. hirsuta (Collins and Dobson 1997;Keum and Li 2004), while in P. pulmonarius HAI 572 and other tested strains, as well as in T. pubescens this element reduced the activity (Galhaup and Haltrich 2001;Tychanowicz et al 2006), which could be explained by species specificity. Laccase induction could be the result of limited selectivity of the metal-responsive promoter in the laccase gene in P. ostreatus, in which transcription can be controlled by several metal ions, including Zn (Faraco et al 2003).…”
Section: Effect Of Trace Elements On Laccase Activitymentioning
confidence: 73%
“…However, Pleurotus pulmonarius and Lentinula edodes SR-1 have been reported to produce only exracellular laccase to decolorize dyes of different spectra without any mediators (Nagai et al 2002). MnP mediated decolorization of azo dyes Direct Blue 15, Direct Green 6, and Congo red by Phanerochaete chrysosporium can be enhanced by the addition of Tween-80 (Ü rek and copper (Tychanowicz et al 2006).Whereas, LiP produced by Trametes versicolor can decolorize Remazol Brilliant Blue R (RBBR) in the presence as well as in the absence of VA (Christian et al 2005). The decolorization ability of WRF can be substantially increased by carefully optimizing the operational conditions such as initial dye concentration, nutrient content of the media, age of fungus and carbon and nitrogen sources (Ozsoy et al 2005;Nilsson et al 2006;Sanghi et al 2006).…”
Section: Biodegradation Of Bleach Plant Effluentsmentioning
confidence: 99%
“…The data obtained in this work showed that laccase was the main ligninolytic enzyme produced by P. pulmonarius in submerged cultures, considering that low Mn peroxidase activities and no lignin peroxidase were detected in the culture filtrates. In the genus Pleurotus, laccases are constitutively produced in small amounts; however, their production can be considerably enhanced by a wide variety of substances, mainly aromatic or phenolic compounds related to lignin or lignin derivatives, such as ferulic acid, 2,5 xylidine, p-anisidine or veratryl alcohol (Leonowicz et al, 2001;Souza et al, 2004;Tychanowicz et al, 2006) In this work, the supplementation of submerged cultures with corn cob extract had a very pronounced effect on the laccase activity in P. pulmonarius. The laccase inducer effect of the soluble plant extract is considered to be related to its phenolic content.…”
Section: Discussionmentioning
confidence: 99%